ATP11B triggers the infiltration of T cells into GBM and intensifies anti-GBM immunity by upregulating and externalizing S1PR1 - Hui Qiu; Ziqin Chen; Jie Chen; Huijuan Yu; Xin Wen; Chang Xu; Gongzhen Liu; Luyijie Chai; Longzhen Zhang; Yilong Guo; Xin Ding (Journal of Translational Medicine)
Abstract Background Insufficient T-cell infiltration in tumours causes immune checkpoint inhibitor (ICI) resistance in glioblastoma (GBM) patients. The aim of this study was to demonstrate a preferable way to facilitate T-cell infiltration and improve the therapeutic effects of ICIs in GBM. Methods Flow cytometry, western blot and immunofluorescence staining were used to detect the effects of ATP11B upregulation on S1PR1 expression and distribution, T-cell infiltration and differentiation. A coculture system and an intracranial GBM model were established to explore the anti-GBM potential of ATP11B/S1PR1 signaling through systemic administration of CD3-DSPE-PEG2K-NHS/ATP11B nanoparticles to specifically deliver ATP11B overexpressing plasmids to T cells. Results S1PR1 deficiency in T cells caused T-cell lymphopenia and systemic immunosuppression in GBM, whereas ATP11B overexpression induced the upregulation and externalization of S1PR1 on T-cell membranes, thus increasing the ability of T cells to eliminate GBM cells. In intracranial GBM models, an ATP11B overexpression plasmid was specifically delivered to T cells in the peripheral blood, bone marrow and spleen, then triggering the infiltration of T cells deeply into the GBM and reversing systemic immunosuppression, ultimately enhancing the therapeutic outcomes of ICIs. Conclusions The upregulation and externalization of S1PR1 on T cells mediated by ATP11B overexpression may be promising immunotherapeutic alternatives for GBM treatment.